Integration of machine learning and bulk sequencing revealed exosome-related gene FOSB was involved in the progression of abdominal aortic aneurysm - Ma, Xianlu; Zhou, Hongjie; Wang, Ren (Frontiers in Cell and Developmental Biology, 2025)
BackgroundAbdominal aortic aneurysm (AAA), characterized by the pathological dilation of the abdominal aorta, was associated with immune response and inflammation. However, the key genes involved in the occurrence and progression of AAA remains unclear.MethodsWe applied Weighted Gene Co-expression Network Analysis (WGCNA) and Support Vector Machine Recursive Feature Elimination (SVM-RFE) to screen for significant genes from the Gene Expression Omnibus (GEO) dataset. The CIBERSORT algorithm was utilized to analyze the correlation between these genes and immune cell infiltration. Additionally, we validated the expression of FosB proto-oncogene, AP-1 transcription factor subunit (FOSB) in a murine model of AAA. FOSB was overexpressed and knocked out in vascular smooth muscle cells (VSMCs). Cell viability and apoptosis were assessed using the CCK-8 assay and flow cytometry, respectively. The levels of MMP2 and MMP9 in the cell supernatants were quantified by ELISA. The expression of contraction-related markers α-SMA and SM22α, and the synthetic marker OPN, was analyzed by qRT-PCR and Western blot.ResultsA total of 44 differentially expressed genes were identified, revealing distinct expression patterns between AAA and normal samples. WGCNA identified two key gene modules that were strongly correlated with immune and inflammatory responses, with the hub genes from these modules enriched in immune-related pathways. FOSB was positively correlated with monocytes, plasma cells, eosinophils, and T follicular helper cells. It was further validated in an AngII-induced AAA mouse model. Overexpression of FOSB significantly increased the expression levels of MMP2 and MMP9 in VSMCs. Additionally, FOSB overexpression inhibited the expression of contractile phenotype markers α-SMA and SM22α, while promoting the expression of synthetic phenotype marker OPN.ConclusionExosome-related gene FOSB was involved in the progression of abdominal aortic aneurysm. FOSB represents a promising potential therapeutic target for mitigating the progression of Abdominal Aortic Aneurysm.